2019
DOI: 10.35608/ruraled.v40i3.779
|View full text |Cite
|
Sign up to set email alerts
|

Superintendents’ Perceptions Regarding the Supervision and Evaluation of Principals in a Rural State

Abstract: The goals for this mixed methods study were to examine superintendents’ perceptions regarding their own supervision and evaluation of principals in a rural state. Five research questions guided the mixed methods inquiry. An online survey tool was used to gather perceptions from superintendents regarding their own evaluation and supervision of principals. Participants solicited included all 48 superintendents from a rural Mountain West state. Out of the participants solicited 23 superintendents agreed to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The learning tools that have been made by the teacher are checked and assessed through instruments, observing the learning process carried out by the teacher and filling out the learning implementation instruments as well as observing how the teacher conducts learning assessments. In addition (Hasan, 2016;Hvidston et al, 2016) suggested that the supervision carried out by the principal aims to shape and improve the ability of teachers in the teaching and learning process. Supervision can help improve professional abilities so that teachers can complete their duties and responsibilities well and create comfortable and enjoyable learning conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The learning tools that have been made by the teacher are checked and assessed through instruments, observing the learning process carried out by the teacher and filling out the learning implementation instruments as well as observing how the teacher conducts learning assessments. In addition (Hasan, 2016;Hvidston et al, 2016) suggested that the supervision carried out by the principal aims to shape and improve the ability of teachers in the teaching and learning process. Supervision can help improve professional abilities so that teachers can complete their duties and responsibilities well and create comfortable and enjoyable learning conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is affirmed in a study of six large school districts, where approximately 76% of novice principals over a 3-year period reported the quality of feedback they received was good or excellent from their evaluations and more than 50% of novice principals reported some type of feedback indicating they needed to show improvement in at least one facet of professional practice (Anderson & Turnbull, 2016). These generally positive perceptions of feedback from the superintendent have not been a hallmark of past principals’ supervision and evaluation as feedback has not been meaningful or frequent (Reeves, 2009) and has not been delivered in a reasonable amount of time sometimes occurring “three to six months after the fact” (Hvidston et al, 2015, p. 25). One superintendent in a study engages his principals in four visits a year focusing “on school improvement, the impact of the data and evidence to support the principals overall assessment” (Zepeda, Lanoue, Price, & Jimenez, 2014, p. 345).…”
Section: Discussionmentioning
confidence: 99%
“…As principals require feedback from the superintendent during the supervision and evaluation cycle to improve instructional leadership (Hvidston, Range, & McKim, 2015), researchers report the unsystematic methods for delivery of these evaluation systems and the lack of meaningful, timely feedback as integral component in the supervision and evaluation of principals (Davis & Hensley, 1999; Ginsberg & Berry, 1990; Harrison & Peterson, 1988; Reeves, 2009; Stronge, 2013). Arne Duncan, former Secretary of Education, stated regarding the importance of feedback in principals’ evaluations, “All of us want really good, honest, comprehensive feedback as to how we’re doing in our jobs.…”
mentioning
confidence: 99%
“…Principals' jobs vary widely: diverse school contexts (e.g., Leithwood et al, 2020) and a range of complex challenges (Grissom et al, 2018) meant that early iterations of principal assessment and accountability tools were overly broad and evinced little consensus regarding how state or local education agencies (SEAs; LEAs) valued leader competencies (Davis et al, 2011). In order to substantiate the case for principal evaluation, research addressing principal evaluation has focused on relationships among evaluator or supervisor training and feedback (Anderson & Turnball, 2016;Hvidston et al, 2015Hvidston et al, , 2018McMohan, et al, 2014;Nielsen & Lavigne, 2020;Sun et al, 2012;Zepeda et al, 2014), goal-setting (Anderson & Turnball, 2016;Hvidston et al, 2015;Nielsen & Lavigne, 2020;Sinnema & Robinson, 2012), and student achievement (Anderson & Turnball, 2016;Fuller & Hollingworth, 2014;Leithwood et al, 2010;McMohan et al, 2014;Nielsen & Lavigne, 2020;Williams et al, 2008). While principal standards may be designed as routes to professional growth, accountability pressures often result in the use of those tools for evaluation rather than development (Nielsen & Lavigne, 2020) which often add to principals' workloads (e.g., Reid, 2021).…”
Section: Principal Evaluation Systemsmentioning
confidence: 99%